Social Background Effects on School and Job Opportunities - Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This paper proposes a theory on how students social background affects their school attainment and job opportunities. We study a setup where students differ in ability and social background, and we analyze the interaction between a school and an employer. Students with disadvantaged background are penalized compared to other students: they receive less teaching and/or are less likely to be hired. A surprising result is that policy aiming to subsidize education for disadvantaged students might in fact decrease their job opportunities.
Keywords: C73; I21; J24; 330